PELAKSANAAN PROGRAM KESELAMATAN DAN KESEHATAN KERJA PADA TENAGA KERJA BAGIAN PENGOLAHAN KELAPA SAWIT PKS RAMBUTAN PTPN-3 TEBING TINGGI TAHUN 2013 - Khoirutun Najihah; Lina Tarigan; Halinda Sari Lubis (Lingkungan dan Kesehatan Kerja, 2013)
The implementation of the Occupational Safety and Health Program at the processing of Oil Palm Kernel produce CPO and kernel PTPN-3 Tebing Tinggi on 2013. Research has done on PKS Rambutan PTPN-3 Tebing Tinggi. This research aims to determine how the the implementation of the Occupational Safety and Health Program at the processing of Oil Palm Kernel produce CPO and kernel includes admissions, boiling (sterelizer), Separation (thressing), stamping (pressing), refining and processing of oil seeds (palm kernel) in PTPN-3 PKS Rambutan Tebing Tinggi North Sumatra. Research of types used in this research was descriptive research with cross-sectional approach.The population in this research is the work force who worked on the processing of Oil Palm Kernel produce CPO and kernel. The population in this study as many as 30 people. The results were analyzed descriptively. The results showed that the implementation of the Occupational Safety and Health Program at the processing of Oil Palm Kernel produce CPO and kernel is performed by workers in the processing is still not up and must be improved for its implementation. OHS program that have been implemented include Standard Operating Procedure (SOP), Job Safety Analysis (JSA), Personal Protective Equipment (PPE), training OHS. On the other hand there are many workers who have implemented programs that have been set by the company. This is due to lack of knowledge and awareness of labor in implementing OHS. Keywords: Implementation Program of Occupational Health and Safety (OHS),workers, processing of Oil Palm Kernel